2021
DOI: 10.1002/btm2.10288
|View full text |Cite
|
Sign up to set email alerts
|

Lipid‐based regulators of immunity

Abstract: Lipids constitute a diverse class of molecular regulators with ubiquitous physiological roles in sustaining life. These carbon‐rich compounds are primarily sourced from exogenous sources and may be used directly as structural cellular building blocks or as a substrate for generating signaling mediators to regulate cell behavior. In both of these roles, lipids play a key role in both immune activation and suppression, leading to inflammation and resolution, respectively. The simple yet elegant structural proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 210 publications
(279 reference statements)
0
6
0
Order By: Relevance
“…Several reports indicate that some TLR-mediated pathways are important driving forces of Th1-type responses. Therefore, these results suggest that the adjuvant mechanism of DOTMA50-LNP differs from that of other LNP adjuvants and may be mediated by pattern recognition receptors (PRRs) other than TLR4 and NLRP3. As one of the mechanisms of lipid immune activation, certain lipopeptides have been shown to act as agonists for TLR2 and activate immune cells. Recent studies have reported that lipids are recognized by the C-type lectin receptor, one of the PRRs, and activate innate and adaptive immunity. , Additionally, several studies have indicated that certain lipids can modulate the activity of immune cells by acting as ligands for G-protein-coupled receptors. , Although several reports indicate the involvement of lipids in immune activation, it remains unclear whether stimulation of such pathways induces Th1 cells, making it challenging to precisely determine the mechanism by which DOTMA50-LNPs induce robust immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that some TLR-mediated pathways are important driving forces of Th1-type responses. Therefore, these results suggest that the adjuvant mechanism of DOTMA50-LNP differs from that of other LNP adjuvants and may be mediated by pattern recognition receptors (PRRs) other than TLR4 and NLRP3. As one of the mechanisms of lipid immune activation, certain lipopeptides have been shown to act as agonists for TLR2 and activate immune cells. Recent studies have reported that lipids are recognized by the C-type lectin receptor, one of the PRRs, and activate innate and adaptive immunity. , Additionally, several studies have indicated that certain lipids can modulate the activity of immune cells by acting as ligands for G-protein-coupled receptors. , Although several reports indicate the involvement of lipids in immune activation, it remains unclear whether stimulation of such pathways induces Th1 cells, making it challenging to precisely determine the mechanism by which DOTMA50-LNPs induce robust immunity.…”
Section: Discussionmentioning
confidence: 99%
“…The expansion of the Th2 subset may be due to the drastic reduction of Treg cells systemically and locally. Previous studies found that SCFAs produced by gut microbiota are important immunomodulators that increase the expression of the transcription factor FOXP3 via inhibition of histone deacetylation to induce the differentiation of Treg cells ( 83 85 ). Eubacterium hallii , Oscillospira and Akkermansia in the gut are involved in the production of SCFAs, primarily acetate, propionate, and butyrate.…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 polyunsaturated fatty acids (PUFAs), such as a-linolenic acid (ALA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA), have been studied for their regulatory impact on immune function [20,21]. Omega-3 competes with omega-6 fatty acids in enzymatic processes, affecting immune cell activities, integrating into cell membranes, influencing signalling, gene expression, lipid mediator production, and playing a role in gene transcription and lipid metabolism, thereby offering insights into immune modulation [22,23]. This lipid modification plays a crucial role in the functions of both innate and adaptive immune cells by affecting membrane composition, fluidity, and receptor interactions.…”
Section: Introductionmentioning
confidence: 99%